A Social Network Analysis of the #AllEyesOnRafah on X Social Media - Wahyuddin, Wahyuddin; Reynaldi, Reynaldi; Marta, Rustono Farady; Engliana, Engliana; Iskandar, Iskandar (Ultimacomm: Jurnal Ilmu Komunikasi, 2024)
Abstract The slogan ‘All Eyes on Rafah’ went viral and became the talk of netizens on social media. The viral hashtag #AllEyesOnRafah on X social media was used to voice solidarity and concern for the humanitarian tragedy that befell the people of Rafah due to the Israeli army's attack. This study, conducted using the rigorous Social Network Analysis (SNA) method and incorporating the computer-mediated communication (CMC) theory and the Homophily theory, seeks to identify influential actors and analyze the communication network of the #AllEyesOnRafah on X social media. The primary data is the posts on social media X with the hashtag #AllEyesOnRafah dated from May 26th to July 4th, 2024. The data collection, processing, and analysis uses the web-based applications Netlytic.org and Gephi software. The SNA analysis reveals 305 nodes and 382 edges centered on several actors. The proximity between actors is 3, showing that the distance between actors is close. Therefore, the interactions are easy to occur. It was also found that the interactions between actors were few and considered uneven; this fact signifies one-way interactions. Such interaction is centered on 10 nodes with the most dominant of which is the @realmarcel1 account. In addition to that, the two most influential actors, @realmarcel1 and @Ta4leaHayam1, consistently scored highest in centrality on the basis of the analysis of degree centrality, closeness centrality, betweenness centrality, and eigenvector centrality. The communication network encouraged X users to support Palestine and informed others.